2009
DOI: 10.1007/s00125-009-1470-0
|View full text |Cite|
|
Sign up to set email alerts
|

Intensive glucose control and macrovascular outcomes in type 2 diabetes

Abstract: Aims/hypothesis Improved glucose control in type 2 diabetes is known to reduce the risk of microvascular events. There is, however, continuing uncertainty about its impact on macrovascular disease. The aim of these analyses was to generate more precise estimates of the effects of more-intensive, compared with less-intensive, glucose control on the risk of major cardiovascular events amongst patients with type 2 diabetes. Methods A prospectively planned group-level metaanalysis in which characteristics of trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
650
3
53

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,051 publications
(731 citation statements)
references
References 17 publications
25
650
3
53
Order By: Relevance
“…These results are broadly in line with the less‐certain effects seen in major randomized trials, and they support the conclusion that improved glycaemic control reduces CV events 6, 17, 18. Participants were newly started on insulin and generally achieved and maintained reasonable glycaemic control during follow‐up in the study, with median HbA1c of 9.3% (78 mmol/mol) at baseline, declining to 7.4% (57 mmol/mol) at the end of year 1 and 7.3% (56 mmol/mol) at the end of year 4.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These results are broadly in line with the less‐certain effects seen in major randomized trials, and they support the conclusion that improved glycaemic control reduces CV events 6, 17, 18. Participants were newly started on insulin and generally achieved and maintained reasonable glycaemic control during follow‐up in the study, with median HbA1c of 9.3% (78 mmol/mol) at baseline, declining to 7.4% (57 mmol/mol) at the end of year 1 and 7.3% (56 mmol/mol) at the end of year 4.…”
Section: Discussionsupporting
confidence: 82%
“…The relationship between HbA1c reduction and CV events in the UKPDS was also suggestive, but uncertain at study end, but again significant at the end of the extension phase (MI, all‐cause mortality), and in study observational analysis 17, 19, 22. Accordingly, the meta‐analyses of these studies also found statistically significant reductions in MI and overall CV events 18, 23.…”
Section: Discussionmentioning
confidence: 91%
“…When the studies are combined, there is consensus that non-fatal coronary episodes are reduced by intensive control, whereas stroke, cardiovascular mortality and total mortality are unaffected [20][21][22][23]. Differences between the Rx 2-3 years -16%…”
Section: Cardiovascular Disease and Glucose Controlmentioning
confidence: 99%
“…Type 2 diabetes mellitus accounts for approximately 90% of diabetes cases, and is primarily caused by insulin resistance, with progressive beta‐cell loss eventually leading to insulin deficiency 2, 3. Poor glycaemic control has been linked to an increased risk of diabetes‐related complications, including retinopathy, nephropathy, autonomic nervous system malfunction, diabetic foot (possibly requiring amputation) and increased risk of stroke and myocardial infarction 4, 5, 6, 7, 8, 9, 10, 11…”
Section: Introductionmentioning
confidence: 99%